Phylogeography of Morella nana: The Wumeng Mountains as a natural geographical isolation boundary on the Yunnan‐Guizhou Plateau - Min Wu; Yu Cheng; Chunxue Jiang; Mingsheng Zhang; Tian Shi; Cai Zhao (Ecology and Evolution, 2024)
Abstract The Yunnan‐Guizhou Plateau (YGP) is characterized by the distinctive isolated habitat of the limestone Karst Islands and features the Wumeng Mountains, which divide the YGP into the two Plateaus of Yunnan and Guizhou. This study aimed to assess the effects of geographic isolation and past climate fluctuation on the distribution of flora in the YGP. To achieve this, we carried out the phylogeographical pattern and genetic structure based on chloroplast and nuclear ribosomal DNA sequence in relation to past (Last Glacial Maximum) and present distributions based on ecological niche modeling for Morella nana, an important wild plant resource and endemic to the YGP once considered a vulnerable species. The results suggest that the genetic and chlorotype network structures of M. nana are divided into at least two groups: cpDNA chlorotype H2 (or dominant nrDNA haplotypes h1 and h2), distributed primarily to the east of the Wumeng Mountains, and cpDNA chlorotypes H1 and H3–H10 (or dominant nrDNA haplotype h2 and h3), distributed to the west of the Wumeng Mountains. A deep genetic split was noted within the two groups to reach 25 steps, especially for the cpDNA fragment variation. This east–west divergence reveals the existence of a natural geographical isolation boundary in the form of the Wumeng Mountains, and supports the existence of at least two glacial refuges during the Quaternary glacial period, along with two genetic diversity center, and at least two large geographic protection units for the important species of M. nana. This study indicates that the phylogeographical pattern of M. nana can be attributed to geographic/environmental isolation caused by the Wumeng Mountains and climate fluctuation during the last glacial maximum, and proposes an effective strategy to protecting this important plant resource.